MANAGEMENT OF PRIMARY HERPETIC GINGIVOSTOMATITIS IN TEENAGER PATIENT : PERAWATAN GINGIVOSTOMATITIS HERPETIKA PRIMER PADA PASIEN REMAJA - Raziv Ganesha (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2020)
Introduction: Primary Herpetic Gingivostomatitis (PHGS) is a primary infection to Herpes Simplex Virus type 1 (HSV-1). PHGS often occurs in pre-school-aged children, but also occur in school-age children and teenager. This case report purpose to discuss management of PHGS in teenager. Case: Patient a 12-year-old with chief complaints are many ulcers in mouth. Ulcer appears after the patient has a fever for 2 days. The patient has never experienced like this before. On Intra Oral examination found ulcers, varying in size, pain in the upper labial, lower labial, lower gingival and lower mucobucalfold. Case Management: patient was given a complete blood count and IgG antigen HSV-1, with reactive results. Patients received treatment in the form of aloe vera extract gel, immunomodulator syrup, and ulcers healed after 12 days of treatment. Conclucion: Primary Herpetic Gingivostomatitis caused by HSV infection. This case often occurs in children but does not rule out the possibility that it can occur in teenager, adults and the elderly. Management in this case is aimed at pain control by topical analgesics and supportive therapy with immunomodulatory. In thiscase, a proper history and examination, accompanied by laboratory examinations, is needed to establish a diagnosis and cooperation between dentists and patients to accelerate recovery.